1983
DOI: 10.1139/v83-377
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of steroidal 4,5- and 5,6-epoxides with strong bases

Abstract: , 2165 (1983). A series of C-3 oxygcnated and unsubstituted (4,5)a, (4,5)P, (5,6)cu, and (5.6)P cpoxy stcroids has been prcparcd, and the reactions of these compounds with strong bases (potassium rert-butoxide, LDA, and LDEA) wcrc investigatcd. Only LDEA gavc rise to product formation; P climination of the cpoxidc to give a P-hydroxy olefin was obscrvecl in this case. The regioselcctivity of product formation is consistcnt with a mechanism of rcarrangcmcnt involving removal of a hydrogen locatcd syr~ to the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Further 'The authors are grateful to a referee for drawing attention to this paper. Can 24-Methylenecholesta-3,5-dien-7-one, 13 Hydrolysis of 7 (25 mg) employing 5% ethanolic KOH (5 mL) at reflux for 2 h afforded, after work-up and ptlc purification, compound …”
Section: Extractions and Separationsmentioning
confidence: 99%
“…Further 'The authors are grateful to a referee for drawing attention to this paper. Can 24-Methylenecholesta-3,5-dien-7-one, 13 Hydrolysis of 7 (25 mg) employing 5% ethanolic KOH (5 mL) at reflux for 2 h afforded, after work-up and ptlc purification, compound …”
Section: Extractions and Separationsmentioning
confidence: 99%
“…F;~y ' y.q " <(I C reassigned following a consideration of the spectra of the compounds (1 8) and a consideration of the effect of the introduction of unsaturation in the 6,7 position (19). Following the successful use of A'.5 en01 acetates as…”
Section: \ /mentioning
confidence: 99%
“…Previous literature data reported the partial characterization of these compounds, [7,10,11] but from these data we were unable to distinguish between the two epoxides due to incoherent NMR results. [10,11] With the techniques now available (NMR spectroscopy and X-ray crystallography) we concluded that several previous NMR assignments are not correct.…”
Section: Oxidation Of 4-cholestene (2)mentioning
confidence: 69%